Evolução dirigida da região variável do anticorpo monoclonal Rituximabe: construção de uma biblioteca para seleção de moléculas Anti-CD20 com alta afinidade via phage display - Bezerra, Marcus Rafael Lobo (2019)
Rituximab is a therapeutic monoclonal antibody used in the treatment of diseases in which the depletion of B cells might be beneficial, such as Non-Hodgkin Lymphoma and rheumatoid arthritis. It is a biopharmaceutical that, currently, the Brazilian’s public health system nedds to import, since there is no national production of this antibody. The mechanisms of action of Rituximab are intrinsically linked to its capacity to interact with CD20 antigen, a membrane protein present on the surface of mature B cells. Therefore, protein engineering strategies, such as directed evolution, may be used towards altering the antigen binding region of this antibody, improving its affinity. Fragments such as scFv (single-chain fragment variable) can be used because they are small and less complex molecules, but retain the amino acids that comprise the variable portion of antibodies. In this work, a library of Rituximab’s scFv gene was constructed, aiming to mature the affinity of this antibody to the CD20 antigen. The variability of the library was obtained through error-prone PCR (epPCR), in which the components of the standard PCR are altered in order to insert random mutations in the DNA sequence. The sequences randomly mutated were cloned into pHEN2 vector, transformed into E. coli to construct the scFv and presented on the phage surface after coinfection with helper phage (VCSM13). The viral particles expressing scFv on the surface were submitted to rounds of selections, based on the interaction of the mutants to a synthetic peptide, corresponding to the native antibody’s epitope. The library has a size of 1.4 x 105 clones and was analyzed by DNA sequencing. The library showed a mutation rate in the DNA sequence of 726 bp of 0.56% (±0.24) and a mutation rate of 1.07% (±0.76) at protein level (242 aa). The selection was performed against the largest extracellular loop of CD20 (biotinylated synthetic peptide). Two rounds of selection were executed in crescent astringent conditions (successive washes to remove low- and non-binding phages). The resulting phages were submitted to PCR with scFv-specific primers and were analyzed by sequencing. It is expected that the observed point mutations might exert an important role on affinity maturation. If these effects are confirmed, it is possible to increase the therapeutic effect of Rituximab, and these mutatnts might be exploited as biopharmaceuticals in different formats, such as bispecific molecules and chimeric antigen receptors (CAR).